IMAGING ASPECTS OF NON-CHOLESTEATOMATOUS CHRONIC OTITIS AND INTRACEREBRAL COMPLICATIONS OF CHOLESTEATOMA IN PATIENTS HOSPITALIZED AND TREATED AT “PROF. N. OBLU” HOSPITAL IN IAȘI - Ariadna Mocrei; Andreea Diana Ilinca; Alexandra Chichirău; Teodora Buznea; Bianca Vornicu; Ana Elena Sirghe; Danisia Haba (Romanian Journal of Medical and Dental Education)
Intracranial infectious complications (such as abscess) are commonly seen in patients with maxillo-facial area infections/inflammation or temporal bone area (generally ear) infections/inflammation. Cholesteatoma is a mass of soft tissue within the middle ear, consisting of keratinized squamous epithelium and keratin accumulation, with or without inflammation of the surrounding tissue. The study aimed to analyze CT and MRI using conventional and modern techniques for evaluating chronic suppurative cholesteatomatous and non-cholesteatomatous otitis in patients admitted urgently to assess the frequency of intracerebral complications. Material and methods: 30 patients with clinical diagnoses of chronic suppurative otitis media (CSOM) underwent high-resolution CT (HRCT) and MRI to assess the extent of the disease and associated complications. The study involved analyzing imaging elements such as epitympanic lesions, ossicular erosions, and the presence of labyrinthitis ossificans. Results showed that 66.7% of the patients had right ear involvement, while 40% had left ear involvement. Common complications detected during CT included erosion of the sinodural angle and tegmen tympani, with abscesses being a major complication in 96.7% of cases. MRI sequences such as T1, T2, Flair, and advanced diffusion-weighted techniques (non-EPI) were used efficiently, detecting abscesses and complications in the middle cranial fossa in 96.7% of cases. Streptococcus pneumoniae was the most frequently encountered germ, highlighting the need for focused prevention and treatment measures. Conclusions: CT is effective in identifying bone destructions and intracranial complications, while MRI, especially with diffusion-weighted sequences, offers superior differentiation of cholesteatoma from other soft tissue lesions and evaluation of its extent. Combining CT and MRI provides a comprehensive and precise evaluation, facilitating efficient clinical management and improving patient prognosis.